Measurement of intraocular pressure in clinically normal Turkish Shepherd Dogs with the rebound tonometer (TonoVet®) and the applanation tonometer (Tono-Pen Vet®) - Kulualp, Kadri; Yurdakul, Ibrahim; Erol, Hanifi; Atalan, Gultekin; Kilic, Servet (Polish Soc Veterinary Sciences Editorial Office, 2018)
The current study was undertaken to establish reference values of intraocular pressure in clinically normal Turkish Shepherd Dogs with the rebound tonometer (TonoVet (R)) and the applanation tonometer (Tono-Pen Vet (R)). Twenty-eight dogs (14 male and 14 female, aged 9 months-9 years, 56 eyes) were used in this study. All animals were healthy and showed no abnormalities in ophthalmic examinations, which consisted of the Schirmer tear test, slit lamp bio-microscopy, and fluorescein staining. The animals were restrained manually without using systemic anesthetics or tranquilizers. IOP was measured in both eyes with a TonoVet (R) and a Tono-Pen Vet (R). In normal dogs, the mean IOP values for all eyes were 17.63 +/- 3.34 mmHg according to the TonoVet (R) and 14.95 +/- 2.92 mmHg according to the Tono-Pen Vet (R). There was no effect of sex, age, or eye side (right vs. left) on the results obtained with either the TonoVet (R) or the Tono-Pen Vet (R). The mean IOP obtained with the rebound tonometer was 2-3 mmHg higher than that measured with the applanation tonometer. The reference data obtained in the present study may assist in diagnostic testing for ophthalmic diseases in Turkish Shepherd Dogs and may promote further studies in this area.
Keywords: applanation tonometry; rebound tonometry; dog; eye; intraocular pressure